ANALISIS AUDIT SUMBER DAYA MANUSIA PADA BADAN AMIL ZAKAT NASIONAL - Indah Wulandari; Padriyansyah (CV. Doki Course and Training, 2023)
The National Amil Zakat Agency for South Sumatra Province is a zakat management agency whose job is to collect and distribute zakat, infaq and alms funds. This study used a qualitative research method, namely analyzing human resource audits at the Amil Zakat Board of South Sumatra Province to assess the effectiveness of the programs being carried out. The collection of data used is interview, observation and documentation. Based on the research results, it was found that planning, selection, compensation for employee services and employee satisfaction at the Amil Zakat Agency of South Sumatra Province were not effective. However, recruitment, training and development activities as well as termination of employment (PHK) have been carried out effectively. Advice that can be given is to make standard procedures in planning, recruitment process, compensation and remuneration as well as employee satisfaction so that turnover decreases or even doesn't exist Abstrak Badan Amil Zakat Nasional Provinsi Sumatera Selatan merupakan badan pengelolaan zakat yang bertugas menghimpun dan mendistribusikan dana zakat, infaq dan sedekah. Penelitian ini menggunakan metode penelitian kualitatif, yaitu menganalisa audit sumber daya manusia pada Badan Amil Zakat Provinsi Sumatera Selatan untuk menilai efektivitas program-program yang dilakukan. Pengumpulan data yang digunakan adalah wawancara, observasi dan dokumentasi. Berdasarkan hasil penelitian yang diperoleh bahwa pada aktivitas perencanaan, seleksi, kompensasi atas jasa karyawan dan kepuasan karyawan pada Badan Amil Zakat Provinsi Sumatera Selatan belum efektif. Namun, pada aktivitas rekrutmen, pelatihan dan pengembangan serta pemutusan hubungan kerja (PHK) sudah dilaksanakan secara efektif. Saran yang bisa diberikan adalah membuat standar prosedur pada perencanaan, proses rekrutmen, kompensasi dan balas jasa serta kepuasan karyawan sehingga mengakibatkan turnover menurun bahkan tidak ada.